A study on disease burden and treatment among patients attending teleconsultation during lockdown period - Yedlapalli, Mounika; Kiran, Sai Pasupula; Potti, Sravani; A., Devikala; Kambar, Chandrakala (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Covid-19 has been announced as a pandemic by the World Health Organization. To maintain social distancing effectively, the Government of India announced a complete lockdown on March 25th, 2020. As there are no proper transport facilities for patients who need health care services, the Government of Andhra Pradesh started 104 sevakendram as a helpline. Medical services were also provided by this 104 sevakendram through teleconsultation with doctors. The aim and objectives of the study were to study the disease pattern and treatment given to patients attending teleconsultations, to analyze the disease burden among the patients attending teleconsultation, to study the treatment given to the patients attending teleconsultation. Methods: It is a retrospective, observational, and analytical study. After prior IEC clearance and permission from teleconsultation authority, we did the study at Dr.YSR Aarogyasri health care trust, Guntur. Data regarding all calls connected to 104 was collected. Detailed information of the calls related to the Medical officer about the age, gender, disease pattern, and treatment given to the patient was collected. Statistical analysis was done using MS excel software. Results: On average, 104 sevakendram received two hundred valid teleconsultations per day. Most of the calls are related to anxiety and these calls constitute twenty four percent. Treatment given was according to probable diagnosis, mostly symptomatic and continuation of the same treatment. Conclusions: 104 sevakendram has played a vital role in meeting the medical and health requirements of the people suffering from different diseases during the lockdown period.